New insights into the mechanisms of multidrug resistance in cancers - Montazami, N; Aghapour, M; Farajnia, S; Baradaran, B (Cellular and Molecular Biology, 2015)
Drug resistance is one of the major obstacles in the treatment of various cancers. Since chemotherapy serves as a most beneficial method for the repression of tumor progression and due to its desirable cell death potency in tumors which reducing metastasis, failure of such a pivotal treatment lead to tumor recurrence and consequent mortality. Multidrug resistance, the principal mechanism by which many cancers develop resistance to chemotherapy drugs, is a major factor in the failure of many forms of chemotherapy. MDR1 overexpression is one form of the multidrug resistance (MDR) phenotype, which can be acquired by patients initially responsive to chemotherapy. In this review, we briefly look inside the recent mechanisms of chemotherapeutic resistance, the MDR1 gene expression in tumors and some novel inhibition-based approaches.